2020
DOI: 10.1177/1091581820972311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Exposure to Microcystin-LR on the Gut Microbiota of Male Mice

Abstract: Increasing evidence indicates that environmental pollutants can change human gut microbiota. Microcystin–leucine arginine (MC-LR), considered a major hazard to mammals, is one of the important contaminants. However, little is known about the long-term influence of MC-LR on gut microbial communities. We aimed to investigate the effect of MC-LR on gut microbiota composition and functions by conducting a chronic exposure of male mice to MC-LR via the oral route. Using 16S rRNA gene sequencing analysis on cecum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Ten and forty microgram per liter MC-LR can induce a decrease in intestinal microbiota diversity and a change in community composition of Procambarus clarkii (Zhang et al, 2020b). Similar phenomena have been observed in mice (Chen et al, 2015;Zhang et al, 2016Zhang et al, , 2020aZhuang et al, 2021) and zebrafish (Li et al, 2019a). Additionally, MC-LR stress can also alter the functional gene profiles of intestinal microbiota in rats, including chitin, starch and limonene metabolism (Lin et al, 2015).…”
Section: Introductionsupporting
confidence: 54%
“…Ten and forty microgram per liter MC-LR can induce a decrease in intestinal microbiota diversity and a change in community composition of Procambarus clarkii (Zhang et al, 2020b). Similar phenomena have been observed in mice (Chen et al, 2015;Zhang et al, 2016Zhang et al, , 2020aZhuang et al, 2021) and zebrafish (Li et al, 2019a). Additionally, MC-LR stress can also alter the functional gene profiles of intestinal microbiota in rats, including chitin, starch and limonene metabolism (Lin et al, 2015).…”
Section: Introductionsupporting
confidence: 54%
“…One study found that mice exposed to MC-LR exhibited a significant increase in Turicibacter and Clostridium levels while showing a substantial decrease in Ruminococcus and Alloprevotella levels [36]. Another study showed that a decrease in Actinobacteria and Saccharibacteria levels was observed in mice exposed to MC-LR [55]. However, most studies have used normal rather than cancer-prone mice.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study revealed that MCs can affect intestinal barrier function by decreasing the expression of cytoskeletal proteins closely linked to Occludin and ZO-1 in IECs and by dose-dependently impairing the integrity of the intestinal barrier [37]. Zhuang et al also discovered that chronic MC-LR contamination of drinking water in mice for 6 months decreased the expression of mRNA for intestinal tight junction Claudin, Occludion, and ZO-1 [38]. The mRNA levels of intestinal epithelial tight junction-related genes (Claudin-5, Occludin, and ZO-1) were significantly reduced in zebrafish reared for 21 days with MC-LR (35 µg/L) [39].…”
Section: Mc-lr Promoted Colorectal Inflammatory Response and Barrier ...mentioning
confidence: 99%